2018
DOI: 10.1074/jbc.ra118.004972
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase D–dependent mTOR complex 1 (mTORC1) activation by glutamine

Abstract: Glutamine is a key nutrient required for sustaining cell proliferation, contributing to nucleotide, protein, and lipid synthesis. The mTOR complex 1 (mTORC1) is a highly conserved protein complex that acts as a sensor of nutrients, relaying signals for the shift from catabolic to anabolic metabolism. Although glutamine plays an important role in mTORC1 activation, the mechanism is not clear. Here we describe a leucine- and Rag-independent mechanism of mTORC1 activation by glutamine that depends on phospholipas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 40 publications
1
27
0
Order By: Relevance
“…In full medium, LAMTOR1 silencing did not affect mTORC1 activation levels (Fig. 7E), consistent with Rag and Ragulator-independent pathways mediating mTORC1 activation, as reported previously 79, 80 . However, upon aa deprivation, LAMTOR1 knockdown in p27 −/− MEFs restored mTOR inhibition, evaluated by measuring p70 S6K1 phosphorylation levels (Fig.…”
Section: Resultssupporting
confidence: 91%
“…In full medium, LAMTOR1 silencing did not affect mTORC1 activation levels (Fig. 7E), consistent with Rag and Ragulator-independent pathways mediating mTORC1 activation, as reported previously 79, 80 . However, upon aa deprivation, LAMTOR1 knockdown in p27 −/− MEFs restored mTOR inhibition, evaluated by measuring p70 S6K1 phosphorylation levels (Fig.…”
Section: Resultssupporting
confidence: 91%
“…On the other hand, a recent study suggested that the addition of dimethyl-α-KG (DM-α-KG), a cell-permeable analog of α-KG, promotes mTORC1 activation even in RAGA/B knockout cells. Moreover, the effect of DM-α-KG on mTORC1 was counteracted by PLD1 inhibition, indicating that α-KG stimulates mTORC1 via the PLD1-RalA-Arf1 axis in addition to RagB [127].…”
Section: Glutamine-dependent Activation Of Mtorc1 Via Arf1 In the Golmentioning
confidence: 98%
“…3 a). Although the mechanisms by which Arf1 induces mTORC1 translocation to the lysosomes are largely unknown, a recent report suggested that phosphatidic acid (PA) generated by the phospholipase D1 (PLD1) acts downstream of Arf1 to promote mTORC1 activation [ 127 ]. Indeed, PLD1 activity appears to be regulated by leucine and more potently by glutamine.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has been reported some channel proteins and metabolic enzymes including IDH1, IDH2, BCAT1, OGDH, GDH, SLC1A4, SLC1A5, GLUL, and GLA were involved in the metabolism of α-ketoglutarate in many cell types [9,[23][24][25][26][27][28][29][30][31], the mechanism of intracellular α-ketoglutarate regulation during HSC activation has not been previously reported. The main metabolic sources of intracellular α-ketoglutarate including glucose and glutamine were kept sufficient in the cell culture medium in our research [32,33], while the expression of channel proteins and metabolic enzymes mentioned above were investigated during HSC activation.…”
Section: Discussionmentioning
confidence: 97%